Cover‐crop water use and productivity in the high plains wheat–fallow crop rotation. Issue 2 (20th January 2021) - Holman, Johnathon D.; Assefa, Yared; Obour, Augustine K.
Abstract: A long fallow period (∼15 mo) in a winter wheat ( Triticum aestivum L.)–fallow rotation (W‐F) cropping system is meant to store soil water for the following crop but loss of soil quality, low precipitation use‐efficiency, and increased cost of fallow management are among its drawbacks. Replacing a portion of the fallow period with a short‐season cover crop may alleviate these drawbacks. The objectives of this study were to evaluate available soil water at planting (ASWPcc ), performance, management, and post‐cover‐crop fallow efficiency, and available soil water at winter wheat planting (ASWPww ) of 12 short‐season cover crops. This field study was conducted from 2008 through 2011 at Garden City, KS. The experimental design was a randomized complete block with split‐split‐plot arrangement. Crop phases were main plot, cover‐crop species was the subplot, and cover‐crop management method (cover crop left standing or hayed) was the split‐split‐plot treatment. Results showed ASWPcc was greater at spring cover‐crop planting than in the fall or winter cover crops. However, water use, productivity, and post‐cover‐crop fallow efficiency were greatest for sole winter triticale (× Triticosecale spp.) or winter legume–triticale mixtures. In addition, ASWPww was 4–27% more for cover crop left standing than hayed cover crops. Post‐cover‐crop precipitation storage was positively related to ASWPww but cover‐crop biomass had a negative linear relationship with ASWPww . We concluded that cover crops left standing stored more soil water than those hayed; however, forage use of the cover crop could provide a dual purpose and economic benefit to improve overall system profitability. Core Ideas: ASWHcc was greater at spring planting than fall. Water use, productivity, and fallow efficiency were greatest for winter triticale. ASWPww was 4–27% more for cover crops left standing than hayed. Post‐cover‐crop precipitation storage was positively related to cover‐crop biomass and ASWPww . Cover‐crop biomass had a negative linear relationship with ASWHcc and wheat planting.